Hernández Delgado, Lourdes; López Valero, Amando; Encabo Fernández, Eduardo; Jerez Martínez, Isabel; Literatura Infantil y lectura dialógica. La formación de educadores desde la investigación, Barcelona, Editorial Octaedro, 2021, 144pp. (Estudios Humanísticos. Filología, 2022)
Reseña